Warisan dunia Situs Sangiran; Persepsi menurut penduduk Sangiran - Sulistyanto, Bambang (Wacana, Journal of the Humanities of Indonesia, 2009)
Cultural heritages are things from the past, which are valued by communities in recent time as part of their nation's culture. In reality, among the community members there are problems that arise as a result of diverse perceptions, due to the fact that each perception is based on own interests as is the case with the Site of Sangiran. On the one hand, the Government, as part of the present community, has an idealistic orientation towards the Site of Sangiran as a cultural heritage which unquestionably needs to be protected for the purpose of scientific knowledge and national identity. The local people around Sangiran Site, on the other hand, consider it as their ancestors' area which possesses valuable contents and advantages to improve their economic condition. This conflict and the consequences (fossil protection on the one hand and fossil trade on the other) have so far not been resolved. Meanwhile, the destruction of the Site of Sangiran as the World Cultural Heritage No. 593 is still continuing.